Chuanxiong Formulae for Migraine: A Systematic Review and Meta-Analysis of High-Quality Randomized Controlled Trials - Shan, Chun-Shuo; Xu, Qing-Qing; Shi, Yi-Hua; Wang, Yong; He, Zhang-Xin; Zheng, Guo-Qing (Frontiers in Pharmacology, 2018)
Objective: Migraine is a complex, prevalent and disabling neurological disorder characterized by recurrent episodes of headache without ideal treatment. We aim to assess the current available evidence of herbal Chuanxiong [Ligusticum chuanxiong Hort. root] formulae for the treatment of migraine according to the high-quality randomized controlled trials (RCTs). Methods: English and Chinese electronic databases were searched from their inceptions until March 2017. The methodological quality of included study was assessed by the Cochrane Collaboration risk of bias tool. RCTs with Cochrane risk of bias (RoB) score ≥ 4 were included in the analyses. Meta-analysis was conducted using RevMan 5.3 software. Publication bias was assessed by funnel plot analysis and Egger’s test. Results: Nineteen RCTs with 1832 participants were identified. The studies investigated the Chuanxiong formulae versus placebo (n = 5), Chuanxiong formulae versus conventional pharmacotherapy (CP) (n = 13 with 15 comparisons), and Chuanxiong formulae plus CP versus CP (n = 1). Meta-analysis indicated that Chuanxiong formulae could reduce frequency, duration, days and pain severity of migraine and improve the total clinical efficacy rate (P < 0.05). Adverse event monitoring was reported in 16 out of 19 studies and occurrence rate of adverse event was low. Conclusion: The findings of present study indicated that Chuanxiong formulae exerted the symptom reliefs of for migraine.